Tailoring Rigid Segments in Dopant-Free Polymeric Hole Transport Materials for Perovskite Quantum Dot Solar Cells - Lee, Dae Hwan; Lim, Seyeong; Kim, Chanhyeok; Lee, Han Uk; Chung, Dasol; Choi, Yelim; Choi, Jongmin; Kim, Younghoon; Cho, Sung Beom; Kim, Hong Il; Park, Taiho (ACS Energy Letters, 2023)
The dominant hole transport material (HTM) used in perovskite quantum dot solar cells (PQD-SCs) is a Spiro-OMeTAD, which inevitably requires doping systems to increase charge mobility. However, the use of deliquescent dopants leads to the degradation of PQD-SCs, necessitating the development of efficient dopant-free HTMs for their commercialization. Here, we designed three types of dopant-free HTMs: Asy-PDTS, Asy-PSDTS, and Asy-PSeDTS. We apply chalcogenide-based fluorinated benzothiadiazole as a rigid segment acceptor unit to generate an effective charge hopping channel, compensating for the impaired electrical property through side chain engineering. The rigid segment is constructed into favorable planar structures of face-to-face stacking by a conformation-locking approach via chalcogenide-fluorine noncovalent interactions (S···F and Se···F). The optimized device using Asy-PSeDTS achieved 15.2% power conversion efficiency (PCE) and maintained 80% of the initial PCE after 40 days, which is the highest PCE and stability among dopant-free HTM-based PQD-SCs so far.
Keywords: Cell-be; Cell/B.E; Cell/BE; Charge mobilities; Commercialisation; Dopant-free; Doping system; Hole transport materials; Power conversion efficiencies; Quantum dot solar cells